HPV Vaccine: Current Data, Efficacy, and Clinical Implications - agnieszka marut; Karolina Kopeć; Aleksandra Bartoszek; Julia Adamiuk; Marta Biskup; Jagoda Misiuk; Adriana Skuba; Katarzyna Załuska; Agnieszka Świdniak; Sylwia Nykiel (Quality in Sport)
Introduction and Purpose: Human papillomavirus (HPV) is a major cause of several cancers, including cervical cancer, and HPV vaccination is an effective method of preventing these diseases, especially before the initiation of sexual activity. The aim of this paper is to review current knowledge regarding HPV vaccines. It seeks to determine their effectiveness and their application in both primary and secondary prevention of HPV-related diseases.